2004
DOI: 10.1007/s10669-004-4803-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Grazing and Climatic Changes on Alpine Vegetation of Tungnath, Garhwal Himalaya, India

Abstract: Effect of grazing and changing climate on vegetation composition of alpine pasture at Tungnath, Garhwal Himalaya was observed. Growth form pattern and phytosociological attributes were analyzed during 1988 under grazed (exposed to extensive grazing) and ungrazed (protected from grazing) conditions. These observations were repeated during 1998. It was observed that number of early growing species and long vegetative growth cycle species had increased at both sites in 1998 in comparison to 1988. Further, some sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 17 publications
1
27
0
Order By: Relevance
“…Barik et al (1992) and Tripathi (2002) have also suggested that low light intensity on the ground floor due to dense overhead canopy may check the growth of seedlings. Although the response of tree seedlings to the changing climate has not yet been fully explored, Nautiyal et al (2004) and Chaturvedi et al (2007) observe that changes in snow pattern and fluctuating temperature affects the distribution and phenology of some plants.…”
Section: Discussionmentioning
confidence: 99%
“…Barik et al (1992) and Tripathi (2002) have also suggested that low light intensity on the ground floor due to dense overhead canopy may check the growth of seedlings. Although the response of tree seedlings to the changing climate has not yet been fully explored, Nautiyal et al (2004) and Chaturvedi et al (2007) observe that changes in snow pattern and fluctuating temperature affects the distribution and phenology of some plants.…”
Section: Discussionmentioning
confidence: 99%
“…About 4000-5000 sheep and goats, 50-70 buffalos and 30-40 horses and mules reach in the alpine pastures each year exerting heavy grazing pressure (Nautiyal et al 2004). (Table 1).…”
Section: Study Areamentioning
confidence: 99%
“…There are some sporadic studies on climate change and grazing pressures in Indian Himalayan temperate and alpine habitats, but they lack any reference of lichens (Nautiyal et al 2004). In the present study, distribution of terricolous lichens in a temperate-alpine habitat of Garhwal Himalayas is analysed along an altitudinal gradient to assess their indicator capability for habitat disturbances.…”
Section: Introductionmentioning
confidence: 98%
“…Among species of the genus Cymbella, 49 were reported from northeastern China (FAN et al 1993, BAO et al 1992, 8 from Xingjiang Province, NW China (YOU et al 2005(YOU et al , 2008, 44 from India (JENA et al 2006, NAUTIYAL et al 2004, and 9 from Japan (HIRANO 1972). One new variety of Cymbella was described from Qinghai Province, NW China (LI et al 2003b).…”
Section: Introductionmentioning
confidence: 99%